Association between parity and gravidity & hypertension and blood pressure: protocol for a systematic review and meta-analysis - Sofia B Ahmed; Sonia Butalia; Magali Robert; Tyrone G Harrison; Sandra M Dumanski; Nabilah Gulamhusein; Badal S B Pattar; Jane A Schulz (BMJ Open)
Introduction Cardiovascular disease is the leading cause of death among women worldwide, and hypertension is one of the most prevalent and modifiable risk factors. Parity and gravidity, independent of pregnancy complications, have each been associated with hypertension, although results are conflicting. Therefore, we propose to estimate the association between parity and gravidity with hypertension and blood pressure in a systematic review of the literature.Methods and analysis A systematic review will be conducted to estimate the association between parity and gravidity and hypertension and blood pressure. Electronic databases (Excerpta Medica Database, Ovid MEDLINE, Cochrane Central Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature Plus and Web of Science) will be searched from inception to January 2025. Two investigators will independently screen identified abstracts and select observational cohort studies, case-control studies and randomised controlled trials examining parity or gravidity and hypertension or blood pressure. Extracted data will include study and population characteristics, comorbidities, parity, gravidity, incidence of hypertension and changes in blood pressure, study quality and risk of bias. If there are sufficient data, they will be summarised using random effects meta-analysis to estimate the pooled risk ratio or odds ratio of hypertension. Stratified and subgroup analyses will be used to explore potential sources of heterogeneity.PROSPERO registration number CRD42024560535.